Menuju Sistem Pendidikan Global - Ananta Saputra (Unisia, 2008)
The liberalization means as the application and cultivation of some strategic initiatives in the educational field, the writer believes that the majority of educational experts will agree with the purpose of the liberal paradigm. But, if it is intended as a free trade, and the cultural commodity of education is the same as the economic one, some of them will refuse it. In the field of education, there are still some centralistic and ceremonial practices, so that there wouldn't be any creativity. Consequently, the quality of Indonesian education is far from any other countries like Malaysia.  In order to catch up the backwardness in education, the experts are expected to bring about the process of autonomy, decentralization, to consider culture of excellence and social welfare as the most important by developing 4 intelligences. Finally, the social prosperity could be obtained under the frame of global education.Keywords: Education, globalization, liberalization, culture, challenge.